HbMADS4, a MADS-box Transcription Factor from Hevea brasiliensis, Negatively Regulates HbSRPP - Li, Hui-Liang; Wei, Li-Ran; Guo, Dong; Wang, Ying; Zhu, Jia-Hong; Chen, Xiong-Ting; Peng, Shi-Qing (Frontiers in Plant Science, 2016)
In plants MADS-box transcription factors play important roles in growth and development. However, no plant MADS-box gene has been identified to have a function related to secondary metabolites regulation. Here, a MADS-box transcription factor gene, designated as HbMADS4, was isolated from Hevea brasiliensis by the yeast one-hybrid experiment to screen the latex cDNA library using the promoter of the gene encoding H. brasiliensis small rubber particle protein (HbSRPP) as bait. HbMADS4 was 984-bp containing 633-bp open reading frame encoding a deduced protein of 230 amino acid residues with a typical conserved MADS-box motif at the N terminus. HbMADS4 was preferentially expressed in the latex, but little expression was detected in the leaves, flowers, and roots. Its expression was inducible by methyl jasmonate and ethylene. Furthermore, transient over-expression and over-expression of HbMADS4 in transgenic tobacco plants significantly suppressed the activity of the HbSRP promoter. Altogether, it is proposed that HbMADS4 is a negative regulator of HbSRPP which participating in the biosynthesis of natural rubber.